A tile waterproof bonding material for building walls

By using waterproof bonding materials of tile with specific ratios, the problems of poor bonding, low durability and poor waterproofing performance of existing tile bonding materials are solved, and high bonding strength, excellent waterproofing and weather resistance are achieved, and the service life of tile is extended.

CN116177946BActive Publication Date: 2025-03-21HUNAN KUANGCHU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211093581.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-08
Publication Date
2025-03-21
Estimated Expiration
2042-09-08

AI Technical Summary

Technical Problem

The existing ceramic tile bonding materials have problems such as poor adhesion, low durability, easy peeling, large environmental pollution and difficult to control construction quality. They also have poor waterproof performance, which makes them prone to safety hazards such as hollowing and falling off of tiles.

Method used

The waterproof bonding material of ceramic tile consists of P.O42.5 cement, quartz powder, river sand, redispersible latex powder, silane-modified polyurethane resin, reinforced fiber, hydrophobic modified polyammonium olefin dispersant, hydrophobic agent, water reducing agent and cellulose ether is used to improve bonding strength, waterproofness and weather resistance through specific ratios and processes.

Benefits of technology

It achieves a firm bond between the tiles and the wall, reduces material costs, extends service life, and improves waterproof, corrosion resistance and high and low temperature resistance, avoiding problems such as tiles falling off and wall water seepage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003837998970000131
    Figure BDA0003837998970000131
  • Figure BDA0003837998970000141
    Figure BDA0003837998970000141
Patent Text Reader

Abstract

The invention discloses a tile waterproof adhesive material for building walls, and relates to the technical field of building materials. The tile waterproof adhesive material disclosed by the invention is composed of the following raw materials in parts by weight: 30-35 parts of P.O42.5 cement, 25-30 parts of quartz powder, 25-30 parts of river sand, 6-12 parts of redispersible latex powder, 3-6 parts of silane-modified polyurethane resin, 0-8 parts of reinforcing fiber, 0-0.3 parts of hydrophobic modified polyacrylate ammonium salt dispersant, 0.2-0.3 parts of water repellent, 0.2-0.3 parts of water reducer and 0.2-3 parts of cellulose ether. The tile waterproof adhesive material prepared by the invention has good bonding, waterproofing, corrosion resistance, aging resistance and high and low temperature resistance, is non-toxic and harmless, and can be used as a waterproof coating and a tile adhesive; the shrinkage rate of the adhesive material is small, and the difference between the early and late shrinkage rates is small, which ensures long-term high bonding strength, reduces costs, and prolongs the service life of the building wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a tile waterproof bonding material for building walls and a production process thereof. Background Art

[0002] With the rapid development of my country's building materials technology and industry, ceramic tiles, as decorative materials for building walls, have the advantages of stable color, durability, easy washing and wear resistance, and are widely used in the market. The traditional ceramic tile construction process uses cement mortar to paste ceramic tiles, and cement and sand are mixed on site for use. However, cement mortar has poor adhesion, low durability, and is easy to peel off, which pollutes the environment, is not conducive to the control of on-site construction quality, and is prone to safety hazards. With the continuous improvement of product performance requirements, ceramic tile adhesive materials specifically used for ceramic tile bonding have appeared on the market, mainly including ceramic tile adhesive, pressure-sensitive adhesive and ceramic tile backing adhesive.

[0003] Tile adhesive is a mixture of cement, sand, mineral admixtures and functional additives in a certain proportion, evenly mixed in a dry state, and mixed into a granular or powdery mixture. When used, water is added in a specified proportion and mixed. It has the characteristics of fast coagulation and hardening speed, large hydration heat, strong heat resistance, and good adhesion. However, it is easy to appear hollowing and falling off after a few years of use. This is mainly because the existing tile adhesive has poor heat-resistant adhesive strength and toughness. It is easy to expand and contract under large temperature differences, resulting in tiny cracks between the tile adhesive and the tile, and then gradually forming hollows and falling off. The existing tile adhesive has poor waterproof performance. It is easy to get moldy, seepage, and wall sweating after more than 5 years of use, causing great safety hazards. Therefore, in order to solve the waterproofing problem, tile adhesive is often combined with a waterproof layer, so that the tile adhesive must not only ensure its own bonding performance, but also have good water retention and uniform drying shrinkage. It should also match the waterproof layer, and the shrinkage and expansion values ​​of the two should not be much different and have good matching. Otherwise, the combination of the two will result in larger-scale tile hollowing and falling off.

[0004] Pressure-sensitive adhesive is made of polymer emulsion, defoamer, dispersant and other additives. After brushing, it takes 2 to 3 hours for a milky white film to form on the surface before paving tiles, which results in a long construction period. In addition, pressure-sensitive adhesive has poor water resistance and low bonding strength, which can easily cause tiles to fall off. Tile back glue is a product composed of polymer emulsion and inorganic silicate. Like pressure-sensitive adhesive, it is brushed on the back of the tile and then covered with cement mortar and laid on the wall. It does not need to wait for drying and has good water resistance, but the construction is troublesome and the price is slightly higher, so it is not suitable for large-scale use.

[0005] However, in addition to the defects of the tile adhesive materials themselves, problems such as environmental dryness and wetness, temperature changes, water absorption rate and size of tiles can all lead to deformation of tiles and tile adhesive materials, resulting in joints and cracks, causing tiles to fall off and water seepage into the walls. Summary of the invention

[0006] The main purpose of the present invention is to provide a waterproof adhesive material for tiles on building walls, which has good bonding, waterproofing, corrosion resistance, aging resistance and high and low temperature resistance, is non-toxic and harmless, and can be used as a waterproof coating and tile adhesive; the adhesive material has a small shrinkage rate, and the difference between early and late shrinkage rates is small, thereby ensuring long-term high bonding strength, reducing costs, and extending the service life of the building wall.

[0007] In order to achieve the purpose of the present invention, the present invention provides a tile waterproof bonding material for building walls, which is composed of the following raw materials in parts by weight: 30-35 parts of P.O42.5 cement, 25-30 parts of quartz powder, 25-30 parts of river sand, 6-12 parts of redispersible latex powder, 3-6 parts of silane-modified polyurethane resin, 0-8 parts of reinforcing fiber, 0-0.3 parts of hydrophobically modified polyacrylate ammonium salt dispersant, 0.2-0.3 parts of water repellent, 0.2-0.3 parts of water reducer and 0.2-3 parts of cellulose ether.

[0008] Furthermore, the redispersible latex powder is composed of HP8029 redispersible latex powder and DM2072P redispersible latex powder in a mass ratio of 3:1.

[0009] Furthermore, the redispersible latex powder is an acrylate / versatate vinyl carbonate (VeoVa) copolymer, and its preparation method specifically comprises the following steps:

[0010] S1. Add sodium dodecyl diphenyl ether disulfonate (DSB), stearic acid polyoxyethylene ether (SG-40), 2 / 3 of the mass of potassium persulfate and water into a reactor, mix well, heat to 85°C, then slowly add tert-butyl carbonate into the reactor, react for 3-4 hours, then slowly add the remaining 1 / 3 of the mass of potassium persulfate, methyl methacrylate and hydroxyethyl methacrylate into the reactor, continue to react for 3-4 hours, and cool to room temperature to obtain an MMA / VeoVa emulsion with a core-shell structure;

[0011] S2. Add an alkaline solution to the above MMA / VeoVa emulsion, adjust the pH value to 10, then add silica sol and stir for 20 to 30 minutes, then add 5wt% polyvinyl pyrrolidone solution and deionized water to control the viscosity of the emulsion below 300mPa.s to obtain the desired feed liquid;

[0012] S3, passing the above-mentioned liquid into a centrifugal spray drying tower, and spray drying at 120-130° C. to obtain the desired acrylate / versatile vinyl carbonate (VeoVa) copolymer.

[0013] Furthermore, the mass ratio of the versatate vinyl carbonate to the methyl methacrylate is 3:1;

[0014] The total mass of versatate and methyl methacrylate is calculated as the total amount of monomers, the amount of sodium dodecyl diphenyl ether disulfonate added is 1% of the total amount of monomers; the amount of stearic acid polyoxyethylene ether added is 1.5-2.5% of the total amount of monomers; the amount of potassium persulfate added is 0.7-0.9% of the total amount of monomers; the amount of hydroxyethyl methacrylate added is 4.5-6% of the total amount of monomers;

[0015] The added amount of the silica sol is 15-20% of the mass of the MMA / VeoVa emulsion; the added amount of the polyvinyl pyrrolidone solution is 8-10% of the mass of the MMA / VeoVa emulsion.

[0016] Furthermore, the silane-modified polyurethane resin is selected from SPUR 1015LM of Momentive High-Tech Materials Group.

[0017] Furthermore, the reinforcing fibers are composed of glass fibers and polypropylene fibers in a mass ratio of 2:3.

[0018] Furthermore, the hydrophobically modified polyacrylate ammonium salt dispersant is selected from the model OROTAN CA2500 provided by ROHMHAAS.

[0019] Furthermore, the water repellent is an organic silicon water repellent (the present invention uses sodium methylsiliconate water repellent); and the water reducing agent is a polycarboxylic acid water reducing agent.

[0020] Furthermore, the cellulose is methyl cellulose ether or hydroxypropyl methyl cellulose ether.

[0021] The present invention also provides a production process of a tile waterproof adhesive material for a building wall, which specifically comprises the following steps:

[0022] (1) Weigh the above raw material components by weight;

[0023] (2) First, reinforcing fibers and hydrophobically modified polyacrylate ammonium salt dispersant are added to a stirrer and stirred for 5 minutes, and then redispersible latex powder, silane-modified polyurethane resin, hydrophobic agent, water reducing agent and cellulose ether are poured into the stirrer and stirred for 10 to 20 minutes until the mixture is uniformly mixed to obtain material A;

[0024] (3) Pour the weighed PO 42.5 cement, quartz powder and river sand into a conical mixer and stir for 10 to 20 minutes to obtain material B;

[0025] (4) Take out material A, divide it into three portions, and pour them into material B in batches. Pour the first portion and stir for 5 minutes, then pour the second portion and stir for 5 minutes, then pour the third portion and stir for 10 to 20 minutes until the mixture is evenly mixed. Finally, measure and package.

[0026] The present invention has achieved the following beneficial effects:

[0027] 1. The tile waterproof bonding material of the present invention combines the characteristics of waterproof material and tile glue. On the basis of waterproofness, it has good bonding effect, high bonding strength, and firm bonding between tiles and substrates, saving materials and costs. It also has a small shrinkage rate, and the difference between early and late shrinkage rates is small, which ensures that it has a high bonding strength for a long time, thereby ensuring that cracks are not easy to form on the wall, and the tiles are not easy to fall off. It has good corrosion resistance, aging resistance and temperature resistance, ensuring that the waterproof bonding material is stable and does not deform, so that hollowing and cracks will not occur between the wall and the tiles, thereby extending the service life of the bonded tiles.

[0028] 2. The present invention utilizes the organic combination of mineral gelling materials and redispersible latex powder, and selects two different types of redispersible latex powders in a specific ratio, which can be filled into the pores of inorganic gelling materials and penetrate into the capillaries, and wrapped on the surface of inorganic gelling materials, forming a film in the pores or on the surface, so that the inorganic gelling materials and the redispersible latex powder become one, and the binding force between the waterproof bonding material and the matrix and the tile is increased, and the bonding strength is high; the two latex powders of the present invention are combined with the gelling material, so that the components can be fully mixed and uniform, and the waterproofness of the present invention is improved, and the impermeability of the bonding material is improved, so that the present invention has excellent weather resistance, aging resistance and bending strength. The present invention uses homemade redispersible latex powder to replace the compound of HP8029 redispersible latex powder and DM2072P redispersible latex powder, which can achieve the same effect, and has better water resistance, temperature resistance, alkali resistance and flexibility.

[0029] 3. The addition of the silane-modified polyurethane resin of the present invention improves the film-forming property of the adhesive material, improves the cohesive force between the components of the present invention, further improves the mechanical strength and bonding strength of the present invention, and also improves the heat resistance, weather resistance, anti-sagging and workability of the present invention; the reinforcing fiber composed of glass fiber and polypropylene fiber, in addition to improving the mechanical strength of the present invention, also improves the shrinkage performance and toughness of the adhesive material, and improves the water resistance of the adhesive material, as well as the bonding strength with the substrate and the tile; the addition of the hydrophobically modified polyacrylate ammonium salt dispersant allows the reinforcing fiber to be evenly dispersed in the system, improves the bonding ability of the reinforcing fiber with other components, and allows the components to be evenly dispersed and fully mixed, improves the adaptability between the organic component and the inorganic component in the components of the present invention, and can meet the low water-cement ratio requirement, improves the anti-seepage performance of the tile waterproof adhesive material, has good workability, and greatly improves the compressive strength and bonding strength of the present invention.

[0030] 4. The present invention adopts a combination of inorganic gelling materials, organic polymers, reinforcing fibers, etc. to combine with each other, so that the components are tightly combined, and the shrinkage deformation of the bonding material due to environmental influences (including temperature, climate, rain, sunshine, etc.) is small, thereby avoiding the tiny deformation caused by the shrinkage of the tile bonding waterproof material, making it have the function of resisting deformation and cracking of the material, improving the tensile strength of the bonding material, and avoiding the hidden danger of tile falling off.

[0031] 5. The tile waterproof adhesive material of the present invention is prepared by combining inorganic gelling materials with redispersible latex powder, silane-modified polyurethane resin and other organic components, through the synergistic effect of inorganic and organic components, and with other preferred components in the system and their dosage ratios, through a suitable lime-sand ratio, a ratio of coarse and fine aggregates with appropriate particle sizes and a specific preparation process. It has excellent waterproofness and bonding strength, small shrinkage deformation, good flexibility, good anti-sagging property, excellent construction performance, and excellent mechanical properties, high temperature resistance, weather resistance, alkali resistance and aging resistance. It is simple to operate and suitable for conventional production. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The tile waterproof adhesive material for building walls of the present invention will be described below in conjunction with specific embodiments.

[0034] The particle size of the quartz powder in the embodiment of the present invention is 40-80 mesh; the particle size of the river sand is 70-110 mesh.

[0035] HP8029 redispersible latex powder is AXILATTM HP 8029 from Hanson, USA;

[0036] DM2072P redispersible latex powder Redispersible EVA latex powder DM 2072P produced by Japan Synthetic Chemical;

[0037] The silane-modified polyurethane resin was selected from SPUR 1015LM of Momentive High-Tech Materials Group;

[0038] The reinforcing fiber is composed of glass fiber and polypropylene fiber in a mass ratio of 2:3;

[0039] The hydrophobically modified polyacrylate ammonium salt dispersant is selected from the model OROTAN CA2500 provided by ROHMHAAS;

[0040] The water repellent is sodium methylsiliconate water repellent.

[0041] Example 1

[0042] A production process of a tile waterproof adhesive material for a building wall, specifically comprising the following steps:

[0043] (1) Weigh by weight: 35 parts of P.O42.5 cement, 30 parts of quartz powder, 25 parts of river sand, 12 parts of redispersible latex powder, 3 parts of silane-modified polyurethane resin, 0.3 parts of water repellent, 0.2 parts of SP409 powdered polycarboxylic acid water reducer and 3 parts of methyl cellulose ether.

[0044] (2) pouring the redispersible latex powder, silane-modified polyurethane resin, water repellent, water reducing agent and cellulose ether into a stirrer and stirring for 10 minutes to obtain material A;

[0045] (3) Pour the weighed PO 42.5 cement, quartz powder and river sand into a conical mixer and stir for 20 minutes to obtain material B;

[0046] (4) Take out material A, divide it into three portions, and pour them into material B in batches. Pour the first portion and stir for 5 minutes, then pour the second portion and stir for 5 minutes, then pour the third portion and stir for 10 to 20 minutes until the mixture is evenly mixed. Finally, measure and package.

[0047] The above-mentioned redispersible latex powder is composed of HP8029 redispersible latex powder and DM2072P redispersible latex powder in a mass ratio of 3:1.

[0048] Example 2

[0049] A production process of a tile waterproof adhesive material for a building wall, specifically comprising the following steps:

[0050] (1) Weigh by weight: 30 parts of P.O42.5 cement, 25 parts of quartz powder, 25 parts of river sand, 6 parts of redispersible latex powder, 6 parts of silane-modified polyurethane resin, 8 parts of reinforcing fiber, 0.3 parts of hydrophobically modified polyacrylate ammonium salt dispersant, 0.2 parts of water repellent, 0.3 parts of SP409 powdered polycarboxylic acid water reducer and 0.2 parts of methyl cellulose ether.

[0051] (2) First, reinforcing fibers and hydrophobically modified polyacrylate ammonium salt dispersant were added to a stirrer and stirred for 5 minutes, and then redispersible latex powder, silane-modified polyurethane resin, hydrophobic agent, water reducing agent and cellulose ether were poured into the stirrer and stirred for 20 minutes to obtain material A;

[0052] (3) Pour the weighed PO 42.5 cement, quartz powder and river sand into a conical mixer and stir for 20 minutes to obtain material B;

[0053] (4) Take out material A, divide it into three portions, and pour them into material B in batches. Pour the first portion and stir for 5 minutes, then pour the second portion and stir for 5 minutes, then pour the third portion and stir for 10 to 20 minutes until the mixture is evenly mixed. Finally, measure and package.

[0054] The above-mentioned redispersible latex powder is composed of HP8029 redispersible latex powder and DM2072P redispersible latex powder in a mass ratio of 3:1.

[0055] Example 3

[0056] The production process of the tile waterproof adhesive material for the building wall of this embodiment is the same as that of Example 2. The specific production process steps refer to Example 2. However, the tile waterproof adhesive material for the building wall of this embodiment is composed of the following raw materials in parts by weight:

[0057] 35 parts of P.O42.5 cement, 25 parts of quartz powder, 30 parts of river sand, 10 parts of redispersible latex powder, 5 parts of silane-modified polyurethane resin, 6 parts of reinforcing fiber, 0.2 parts of hydrophobically modified polyacrylate ammonium salt dispersant, 0.2 parts of water repellent, 0.3 parts of SP409 powder polycarboxylate water reducer and 1 part of hydroxypropyl methylcellulose ether.

[0058] The above-mentioned redispersible latex powder is composed of HP8029 redispersible latex powder and DM2072P redispersible latex powder in a mass ratio of 3:1.

[0059] Example 4

[0060] The production process of the tile waterproof adhesive material for the building wall of this embodiment is the same as that of Example 2. The specific production process steps refer to Example 2. However, the tile waterproof adhesive material for the building wall of this embodiment is composed of the following raw materials in parts by weight:

[0061] 35 parts of P.O42.5 cement, 25 parts of quartz powder, 25 parts of river sand, 10 parts of redispersible latex powder, 4 parts of silane-modified polyurethane resin, 3 parts of reinforcing fiber, 0.1 parts of hydrophobically modified polyacrylate ammonium salt dispersant, 0.3 parts of water repellent, 0.2 parts of SP409 powder polycarboxylate water reducer and 2 parts of hydroxypropyl methylcellulose ether.

[0062] The above-mentioned redispersible latex powder is an acrylate / versatate vinyl carbonate (VeoVa) copolymer, and its preparation method specifically comprises the following steps, calculated by weight:

[0063] S1, 0.4 parts of sodium dodecyl diphenyl ether disulfonate (DSB), 0.6 parts of stearic acid polyoxyethylene ether (SG-40), 0.2 parts of potassium persulfate and 45 parts of deionized water were added to a reactor, mixed evenly, heated to 85°C, and then 30 parts of tert-butyl ester were slowly added to the reactor, reacted for 3 hours, and then the remaining 0.1 parts of potassium persulfate, 10 parts of methyl methacrylate and 1.8 parts of hydroxyethyl methacrylate were slowly added to the reactor, and the reaction was continued for 4 hours, and cooled to room temperature to obtain an MMA / VeoVa emulsion with a core-shell structure;

[0064] S2. Add 5 wt% NaOH solution to 100 parts of MMA / VeoVa emulsion, adjust the pH value to 10, then add 15 parts of 30% silica sol (solid content in silica sol is 30%) and stir for 30 min, then add 8 parts of 5 wt% polyvinyl pyrrolidone solution and appropriate amount of deionized water to control the viscosity of the emulsion below 300 mPa.s and the solid content to 40±2%, to obtain the desired feed liquid;

[0065] S3. The above-mentioned feed liquid is passed into a centrifugal spray drying tower, spray-dried at 130° C., and sieved through 200 meshes to obtain the desired acrylate / versatile vinyl carbonate (VeoVa) copolymer.

[0066] Example 5

[0067] The production process of the tile waterproof adhesive material for the building wall of this embodiment is the same as that of Example 2. The specific production process steps refer to Example 2. However, the tile waterproof adhesive material for the building wall of this embodiment is composed of the following raw materials in parts by weight:

[0068] 35 parts of P.O42.5 cement, 30 parts of quartz powder, 30 parts of river sand, 10 parts of redispersible latex powder, 4 parts of silane-modified polyurethane resin, 0.3 parts of water repellent, 0.2 parts of SP409 powder polycarboxylate water reducer and 1 part of hydroxypropyl methylcellulose ether.

[0069] The above-mentioned redispersible latex powder is an acrylate / versatate vinyl carbonate (VeoVa) copolymer, and its preparation method specifically comprises the following steps, calculated by weight:

[0070] S1, 0.4 parts of sodium dodecyl diphenyl ether disulfonate (DSB), 1.0 parts of stearic acid polyoxyethylene ether (SG-40), 0.24 parts of potassium persulfate and 48 parts of deionized water were added to a reactor, mixed evenly, heated to 85°C, and then 30 parts of tert-butyl ester were slowly added to the reactor, reacted for 4 hours, and then the remaining 0.12 parts of potassium persulfate, 10 parts of methyl methacrylate and 2.4 parts of hydroxyethyl methacrylate were slowly added to the reactor, and the reaction was continued for 4 hours, and cooled to room temperature to obtain an MMA / VeoVa emulsion with a core-shell structure;

[0071] S2. Add 5 wt% NaOH solution to 100 parts of MMA / VeoVa emulsion, adjust the pH value to 10, then add 20 parts of 30% silica sol (solid content in silica sol is 30%) and stir for 30 min, then add 10 parts of 5 wt% polyvinyl pyrrolidone solution and appropriate amount of deionized water to control the viscosity of the emulsion below 300 mPa.s and the solid content to 40±2%, to obtain the desired feed liquid;

[0072] S3. The above-mentioned feed liquid is passed into a centrifugal spray drying tower, spray-dried at 130° C., and sieved through 200 meshes to obtain the desired acrylate / versatile vinyl carbonate (VeoVa) copolymer.

[0073] Example 6

[0074] The production process of the tile waterproof adhesive material for the building wall of this embodiment is the same as that of Example 2. The specific production process steps refer to Example 2. However, the tile waterproof adhesive material for the building wall of this embodiment is composed of the following raw materials in parts by weight:

[0075] 32 parts of P.O42.5 cement, 30 parts of quartz powder, 25 parts of river sand, 8 parts of redispersible latex powder, 4 parts of silane-modified polyurethane resin, 5 parts of reinforcing fiber, 0.2 parts of hydrophobically modified polyacrylate ammonium salt dispersant, 0.3 parts of water repellent, 0.2 parts of SP409 powder polycarboxylic acid water reducer and 0.5 parts of hydroxypropyl methylcellulose ether.

[0076] The above-mentioned redispersible latex powder is an acrylate / versatate vinyl carbonate (VeoVa) copolymer, and its preparation method specifically comprises the following steps, calculated by weight:

[0077] S1, 0.4 parts of sodium dodecyl diphenyl ether disulfonate (DSB), 0.8 parts of stearic acid polyoxyethylene ether (SG-40), 0.24 parts of potassium persulfate and 46 parts of deionized water were added to a reactor, mixed evenly, heated to 85°C, and then 30 parts of tert-butyl ester were slowly added to the reactor, reacted for 4 hours, and then the remaining 0.12 parts of potassium persulfate, 10 parts of methyl methacrylate and 2 parts of hydroxyethyl methacrylate were slowly added to the reactor, and the reaction was continued for 4 hours, and cooled to room temperature to obtain an MMA / VeoVa emulsion with a core-shell structure;

[0078] S2. Add 5 wt% NaOH solution to 100 parts of MMA / VeoVa emulsion, adjust the pH value to 10, then add 18 parts of 30% silica sol (solid content in silica sol is 30%) and stir for 30 min, then add 9 parts of 5 wt% polyvinyl pyrrolidone solution and appropriate amount of deionized water to control the viscosity of the emulsion below 300 mPa.s and the solid content to 40±2%, to obtain the desired feed liquid;

[0079] S3. The above-mentioned feed liquid is passed into a centrifugal spray drying tower, spray-dried at 130° C., and sieved through 200 meshes to obtain the desired acrylate / versatile vinyl carbonate (VeoVa) copolymer.

[0080] Comparative Example 1

[0081] The production process of the tile waterproof adhesive material in this comparative example 1 is the same as that in Example 3, and the specific process steps refer to Example 3. The difference is that the redispersible latex powder used in this comparative example 3 is HP8029 redispersible latex powder.

[0082] Comparative Example 2

[0083] The production process of the tile waterproof adhesive material in this comparative example 2 is the same as that in Example 3, and the specific process steps refer to Example 3. The difference is that in this comparative example 2, no silane-modified polyurethane resin is added.

[0084] Comparative Example 3

[0085] The production process of the tile waterproof adhesive material in this comparative example 3 is the same as that in Example 3, and the specific process steps refer to Example 3. The difference is that in this comparative example 3, no hydrophobically modified polyacrylate ammonium salt dispersant is added.

[0086] Comparative Example 4

[0087] The production process of the tile waterproof adhesive material in this comparative example 4 is the same as that in Example 6, and the specific process steps refer to Example 6, except that the preparation method of the MMA / VeoVa copolymer in this comparative example 4, by weight, specifically includes the following steps:

[0088] S1, 0.4 parts of sodium dodecyl diphenyl ether disulfonate (DSB), 0.8 parts of stearic acid polyoxyethylene ether (SG-40), 0.24 parts of potassium persulfate and 46 parts of deionized water were added to a reactor, mixed evenly, heated to 85°C, and then 30 parts of tert-butyl ester were slowly added to the reactor, reacted for 4 hours, and then the remaining 0.12 parts of potassium persulfate, 10 parts of methyl methacrylate and 2 parts of hydroxyethyl methacrylate were slowly added to the reactor, and the reaction was continued for 4 hours, and cooled to room temperature to obtain an MMA / VeoVa emulsion with a core-shell structure;

[0089] S2, add 5wt% NaOH solution to 100 parts of MMA / VeoVa emulsion, adjust the pH value to 10, then add 9 parts of 5wt% polyvinyl pyrrolidone solution and an appropriate amount of deionized water to control the viscosity of the emulsion to below 300mPa.s and the solid content to 40±2%, to obtain the desired feed liquid;

[0090] S3. The above-mentioned feed liquid is passed into a centrifugal spray drying tower, spray-dried at 130° C., and sieved through 200 meshes to obtain the desired acrylate / versatile vinyl carbonate (VeoVa) copolymer.

[0091] Comparative Example 5

[0092] The production process of the tile waterproof adhesive material in this comparative example 5 is the same as that in Example 6, and the specific process steps refer to Example 6, except that the preparation method of the redispersible latex powder in this comparative example 5 is MMA / BA copolymer, which specifically includes the following steps by weight:

[0093] S1, 0.4 parts of sodium dodecyl diphenyl ether disulfonate (DSB), 0.8 parts of stearic acid polyoxyethylene ether (SG-40), 0.24 parts of potassium persulfate and 46 parts of deionized water were added to a reactor, mixed evenly, heated to 85°C, and then 27 parts of butyl acrylate (BA) were slowly added to the reactor, reacted for 4 hours, and then the remaining 0.12 parts of potassium persulfate, 13 parts of methyl methacrylate and 2 parts of hydroxyethyl methacrylate were slowly added to the reactor, and the reaction was continued for 4 hours, and cooled to room temperature to obtain an MMA / BA emulsion with a core-shell structure;

[0094] S2. Add 5 wt% NaOH solution to 100 parts of MMA / BA emulsion, adjust the pH value to 10, then add 18 parts of 30% silica sol and stir for 30 minutes, then add 9 parts of 5 wt% polyvinyl pyrrolidone solution and an appropriate amount of deionized water to control the viscosity of the emulsion to below 300 mPa.s and the solid content to 40±2%, to obtain the desired feed liquid;

[0095] S3. The above-mentioned feed liquid is passed into a centrifugal spray drying tower, spray-dried at 130° C., and sieved through 200 meshes to obtain the desired acrylate / versatile vinyl carbonate (VeoVa) copolymer.

[0096] Comparative Example 6

[0097] The production process of the tile waterproof adhesive material in this comparative example 6 is the same as that in Example 6, and the specific process steps refer to Example 6. The difference is that silane-modified polyurethane resin is not added in this comparative example 6.

[0098] The method of using the tile waterproof adhesive material of the present invention is as follows: the waterproof adhesive material: water = 1:0.2-0.25, and the ingredients are mixed thoroughly and evenly; since the waterproof adhesive material contains a polymer adhesive, the viscosity becomes larger, and the spatula should be kept smooth during plastering, and the construction time should be properly controlled during calendering. The reference dosage is: 1.2-1.5 kg / m 2 .

[0099] The tile waterproof adhesive materials of Examples 1 to 6 of the present invention and Comparative Examples 1 to 6 were subjected to performance tests according to the industry standards of JC / T984-2011 and JC / T547-2017. The test results are shown in Table 1 below.

[0100] Table 1 Performance test results of the tile waterproof adhesive material of the present invention

[0101]

[0102] It can be seen from the results in Table 1 that the tile waterproof adhesive material of the present invention has high mechanical strength and bonding strength, excellent water resistance, alkali resistance, high and low temperature resistance, and also has good waterproofness and anti-aging properties.

[0103] Table 2 Performance test results of comparative examples 1-6

[0104]

[0105] From the results of Table 1 and Table 2, it can be seen that the addition of the redispersible latex powder, silane-modified polyurethane resin and hydrophobically modified polyacrylate ammonium salt dispersant of the present invention, in combination with other components of the present invention, significantly improves the comprehensive performance of the waterproof adhesive material of the present invention. The self-made acrylate / versatate vinyl ester copolymer of the present invention can replace the existing dispersible latex powder used in combination, so that the present invention has excellent waterproof bonding function.

[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A tile waterproof adhesive material for building walls, characterized in that: The invention is composed of the following raw materials in parts by weight: 30-35 parts of P.O42.5 cement, 25-30 parts of quartz powder, 25-30 parts of river sand, 6-12 parts of redispersible latex powder, 3-6 parts of silane-modified polyurethane resin, 0-8 parts of reinforcing fiber, 0-0.3 parts of hydrophobic modified polyacrylate ammonium salt dispersant, 0.2-0.3 parts of water repellent, 0.2-0.3 parts of water reducing agent and 0.2-3 parts of cellulose ether; The redispersible latex powder is an acrylate / venereal carbonate (VeoVa) copolymer, and its preparation method specifically comprises the following steps: S1. Add sodium dodecyl diphenyl ether disulfonate (DSB), stearic acid polyoxyethylene ether (SG-40), 2 / 3 of the mass of potassium persulfate and water into a reactor, mix well, heat to 85°C, then slowly add tert-butyl carbonate into the reactor, react for 3-4 hours, then slowly add the remaining 1 / 3 of the mass of potassium persulfate, methyl methacrylate and hydroxyethyl methacrylate into the reactor, continue to react for 3-4 hours, cool to room temperature, and obtain an MMA / VeoVa emulsion with a core-shell structure; S2, adding alkaline solution to the above MMA / VeoVa emulsion, adjusting the pH value to 10, then adding silica sol and stirring for 20 to 30 minutes, and then adding 5wt% polyvinyl pyrrolidone solution and deionized water to control the viscosity of the emulsion below 300mPa.s to obtain the desired feed liquid; S3. Pass the above-mentioned liquid into a centrifugal spray drying tower and spray dry it at 120-130° C. to obtain the desired acrylate / versatate vinyl carbonate (VeoVa) copolymer.

2. The tile waterproof adhesive material for building walls according to claim 1, characterized in that: The mass ratio of the tert-butyl vinyl carbonate to the methyl methacrylate is 3:1; The total mass of versatate vinyl carbonate and methyl methacrylate is calculated as the total amount of monomers, the amount of sodium dodecyl diphenyl ether disulfonate added is 1% of the total amount of monomers; the amount of stearic acid polyoxyethylene ether added is 1.5-2.5% of the total amount of monomers; the amount of potassium persulfate added is 0.7-0.9% of the total amount of monomers; the amount of hydroxyethyl methacrylate added is 4.5-6% of the total amount of monomers; The amount of the silica sol added is 15-20% of the mass of the MMA / VeoVa emulsion; the amount of the polyvinyl pyrrolidone solution added is 8-10% of the mass of the MMA / VeoVa emulsion.

3. The tile waterproof adhesive material for building walls according to claim 1, characterized in that: The silane-modified polyurethane resin is selected from SPUR 1015LM of Momentive High-Tech Materials Group.

4. The tile waterproof adhesive material for building walls according to claim 1, characterized in that: The reinforcing fibers are composed of glass fibers and polypropylene fibers in a mass ratio of 2:

3.

5. The tile waterproof adhesive material for building walls according to claim 1, characterized in that: The hydrophobically modified polyacrylate ammonium salt dispersant is selected from the OROTAN CA 2500 model provided by ROHMHAAS.

6. The tile waterproof adhesive material for building walls according to claim 1, characterized in that: The water repellent is sodium methylsiliconate water repellent; the water reducing agent is polycarboxylic acid water reducing agent.

7. The tile waterproof adhesive material for building walls according to claim 1, characterized in that: The cellulose is methyl cellulose ether or hydroxypropyl methyl cellulose ether.

8. A production process of a tile waterproof adhesive material for building walls as claimed in any one of claims 1 to 7, characterized in that: The specific steps include: (1) Weighing raw material components by weight, the raw material composition is: 30-35 parts of P.O42.5 cement, 25-30 parts of quartz powder, 25-30 parts of river sand, 6-12 parts of redispersible latex powder, 3-6 parts of silane-modified polyurethane resin, 0-8 parts of reinforcing fiber, 0-0.3 parts of hydrophobically modified polyacrylate ammonium salt dispersant, 0.2-0.3 parts of water repellent, 0.2-0.3 parts of water reducing agent and 0.2-3 parts of cellulose ether; (2) First, add the reinforcing fiber and the hydrophobically modified polyacrylate ammonium salt dispersant into a stirrer and stir for 5 minutes. Then, pour the redispersible latex powder, silane-modified polyurethane resin, water repellent, water reducing agent and cellulose ether into the stirrer and stir for 10 to 20 minutes until the mixture is evenly mixed to obtain material A. (3) Pour the weighed PO 42.5 cement, quartz powder and river sand into a conical mixer and stir for 10 to 20 minutes to obtain material B; (4) Take out material A, divide it into three portions, and pour them into material B in batches. Pour the first portion and stir for 5 minutes, then pour the second portion and stir for 5 minutes, then pour the third portion and stir for 10 to 20 minutes until it is evenly mixed. Finally, measure and package.

Citation Information

Patent Citations

  • Interface treating agent for ceramic brick

    CN104016637A

  • High-adhesion and high-weather-resistance ceramic tile adhesive mortar and preparation method thereof

    CN114804787A